New geometric methods for prove existence three-dimensional linear [97, 3, 87] 11 and [143, 3, 131] 13 codes - Nada Yahya; Mustafa Salim (مجلة التربية والعلم, 2019)
In this paper we applied new geometric methods for prove existence three dimensional linear [97,3 ,87]11 and [143,3,131]13 codes  theorems [(1.4.4), (1.5.5)].